Les problèmes de droit international de l’Arctique - Pharand, Donat (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1989)
The territorial sovereignty over Alaska, the Arctic islands of the Soviet Union, Svalbard, Greenland and the Canadian Arctic Archipelago poses no problem, but the continental shelf off those territories and islands has yet to be delimited between the five Arctic States: Alaska, the Soviet Union, Norway, Denmark and Canada. Beyond the continental shelf, the mineral resources of the deep sea-bed should normally form part of the common heritage of mankind, but their presence has not yet been determined. The Arctic Ocean, in spite of the permanent presence of ice, is subject to the freedoms of the seas. The straits of the Northeast Passage are internal waters of the Soviet Union, at least since the establishment of straight baselines in 1985 (presumably, under the Territorial Sea Convention to which the USSR is a Party) and, possibly before, by way of historic title. Under the Convention, a right of innocent passage would exist but not if they are historic waters. The waters of the Northwest Passage are internal waters of Canada since their enclosure by straight baselines in 1985, under customary international law, and no right of passage exists. The sovereignty of Arctic States extends to the air space above their territory, internal waters and territorial sea. There is no right of over flight above those areas, outside of the I.C.A.O. Conventions. The Arctic Ocean being a semi-enclosed sea, bordering States should cooperate under the new Law of the Sea Convention in the exploitation of the living resources, the protection of the marine environment and the conduct of scientific research. This cooperation could best be attained by the creation of an Arctic Basin Council composed of all Arctic States and, possibly, the Nordic countries.